The limits of going global: The case of "Ottoman Enlightenment(s)" - Sarēgiannēs, Marinos (History compass, 2020)
The paper seeks to summarize the discussions of the last two decades on the existence of a phenomenon that can be named "Ottoman Enlightenment." It discusses the German debates on Reinhardt Schulze's suggestion of an "Islamic Enlightenment," as well as more recent studies on the emergence of a different view of the nature and the world in Istanbul during the first decades of the 18th century. These debates are analyzed in the context of different definitions of "Enlightenment," as well as of the relations between different ethnolinguistic groups within the Ottoman Empire. The paper emphasizes the axes of a "democratization of knowledge" or the "massive diffusion of individual reasoning as a legitimate source of truth," on the one hand, and the procedure of a "disenchantment of the world" as it is connected with the Enlightenment phenomenon, on the other. It suggests that, whereas we may trace certain parallels of such procedures between the Ottoman and the Western and Central European model, the lack of integration of such ideas in the curriculum of institutional education in the Ottoman Empire might have been the most important obstacle that kept these ideas from being transformed into a real "Ottoman Enlightenment."